Ultrasound analysis of a canine patient with renal disease and chronic liver disease undergoing treatment with intravenous stem cells - Carandina, Luciana da Silva [UNESP]; Sabino, Emanuelle Guidugli [UNESP]; Babicsak, Viviam Rocco [UNESP]; Vulcano, Luiz Carlos [UNESP]; Machado, Vania Maria de Vasconcelos [UNESP]; Pires Ferreira, Francisco Pupo [UNESP] (Univ Federal Rural Pernambuco, 2011)
With the improvement in quality of life of animals, it is increasingly frequent clinical care of elderly patients, which present renal disorders, including chronic renal failure. Recent studies report the use of stem cells to treat renal failure, which would improve the levels of urea and creatinine, and in renal ultrasound evaluation. With the present work, the idea is to report a case of ultrasonographic evaluation in a patient with chronic renal failure, liver disease and splenic nodule, which underwent stem cell therapy, where there was an improvement in the sonographic evaluation of part of the liver.
Keywords: ultrasonography; stem cell; liver; renal failure